Expression of Progesterone Receptor Membrane Component 1 (PGRMC1) in Follicular and Luteal Tissues in Goats – Effect of Short-term Concentrate Supplementation - Mohammed, N. H.; ShikhMaidin, M.; Yong, C. S. Y.; Ling, K. H.; Martin, G. B. (Tropical Animal Science Journal, 2025)
This study evaluated the effects of short-term supplementation with concentrate on ovulation rate, plasma progesterone concentrations and gene expression for Progesterone Receptor Membrane Component 1 (PGRMC1) in ovarian tissues of Boer goats. Twenty females were allocated to two groups: 1) Control, receiving a maintenance diet consisting of 70% Napier grass plus 30% concentrate (4.45 MJ/day); 2) Supplemented, receiving twice their required metabolizable energy for maintenance by adding extra concentrate (8.90 MJ/day). The dietary treatments were applied for 25 days, beginning 5 days before (Day 5) CIDR removal (Day 0). On Day 19, the ovulation rate was estimated by trans-rectal ultrasonographic scanning. Blood was sampled for progesterone (P4) analysis every 2 days, from Days 9 to 27. On Day 27, the level of expression of PGRMC1 was assessed in follicles and corpora lutea. The ovulation rate was not affected by treatment (Control 1.00 ± 0.24; Supplemented 1.25 ± 0.25). Over Days 13 to 27, plasma P4 concentrations were significantly (p<0.05) greater in the Supplemented group than in the Control group. The expression of PGRMC1 in follicular and luteal tissues was greater in the Supplemented group than in the Control group (p<0.05). There was a positive correlation between PGRMC1 expression and P4 concentration (r= 0.65, p<0.05). It was concluded that, in goats, short-term concentrate supplementation could increase P4 concentrations, at least in part, by influencing the expression of PGRMC1. This finding suggests that short-term concentrate supplementation can support embryo development during the luteal phase and early stages of pregnancy.